Personality traits and quality of life: a cross-sectional study in a middle-aged Iranian general population - Danial Habibi; Roqayeh Parsaei; Hamidreza Roohafza; Awat Feizi (Health and Quality of Life Outcomes)
Abstract Introduction Despite considerable research on the association between Personality Traits (PT) and Quality of Life (QoL) in patients and older adults, this association remains poorly understood among the middle-aged general population.This investigation examines how each PT is associated with total QoL and its dimensions. Methods The present investigation utilized data collected from a cross-sectional survey involving 786 families in Isfahan (644 female/wife respondents), Iran. QoL and PT were assessed using the validated WHOQOL-BREF and NEO-FFI questionnaires. Other data including demographic and socioeconomic status (SES) were also collected. Statistical analyses included bivariate correlation and simple and multiple linear and logistic regressions. Results Mean value of Psychological health [Mean difference = -4.34, P = 0.003], Physical health [mean difference = -3.93, P = 0.004], and total score of QoL [mean difference = -3.21, P = 0.049] were all significantly lower in women than men. Higher SES score was consistently associated with greater QoL scores (r > 0, P < 0.05). The physical domain and total QoL scores have been negatively correlated with the spouse's age (r < 0, P < 0.05). In crude and adjusted models, higher Neuroticism scores were inversly associated with higher scores of all QoL domains and total QoL (OR < 1, P < 0.05, for all models) while others personality traits except Openness showed a direct association (OR > 1, P < 0.05). Linear regression analysis also confirmed that higher Neuroticism scores were linked to poorer QoL scores (Betacoefficient < 0, P < 0.05), while all other traits, except Openness, showed a positive association (Betacoefficient > 0, P < 0.05). Conclusion This study provides robust evidence about the significant association of PT with QoL outcomes in middle aged people. This significant association highlights the importance of considering these traits in clinical applications, as tailored interventions based on personality profiles can effectively enhance the well-being of middle-aged individuals.